The Impact of Knowledge Creation and Technology Education on New Product Development - Papoutsakis, Haris (Design and Technology Education: An International Journal, 2006)
The aim of this article is to investigate and bring to light the constructive impact of Knowledge Creation and Technology Education on the process of New Product Development. This is done under the competence-based perspective of the organization, where knowledge is the point of departure and the individual – in this case the industrial employee – is the relevant unit of analysis ten research enablers were exploited in order to evaluate how New Product Development is influenced by knowledge (tacit and explicit), Knowledge Creation (socialization, externalization, combination and internalization) and Technology Education (competence, skills, commitment and fit). Surveys collected from 486 employees, of 51 industrial companies in Spain, were analyzed in order to test the hypothesis. The results of this study allow us to draw conclusions on the significance of the impact that knowledge, Knowledge Creation and Technology Education have, each one on its own and all three combined, on New Product Development.